Dynamic of psychological and clinical characteristics of patients with retinal vein occlusion in the process of complex therapy - Udovenko, Ірина; Kharchenko, Дмитро (Psychosomatic Medicine and General Practice, 2018)
The dynamics of psychological and clinical characteristics of patients with retinal vein occlusion in the process of complex therapy was studied. It is proved that the complex nosological-oriented pharmacological and psychological therapy used in treatment of patients with retinal vein occlusion contributes to more effective treatment and improves the psycho-emotional state of patients. The use of combined polymodal blocks of perceptual psychotherapy is discussed.